Babies' Portal Website Hearing Aid Section: Assessment by Audiologists - Bastos, Bárbara Guimarães (Int Arch Otorhinolaryngol, 2014)
Introduction The family has ultimate responsibility for decisions about the use and care during the daily routine and problem solving in the manipulation of hearing aids (HA) in infants and children. Objective The purpose of the study was to assess technical and content quality of Babies' Portal website Hearing Aid section by audiologists. Methods Letters and e-mails were sent inviting professionals to surf the website and anonymously fill out an online form with 58 questions covering demographic data as well as the website's technical (Emory questionnaire with the subscales of accuracy, authorship, updates, public, navigation, links, and structure) and content quality. Results A total of 109 professionals (tree men and 106 women) with mean age of 31.6 years participated in the study. Emory percentage scores ranged from 90.1 to 96.7%. The Hearing Aid section contents were considered good or very good. Conclusion The website was deemed to have good technical and content quality, being suitable to supplement informational counseling to parents of hearing-impaired children fitted with hearing aids.